E-Module about “Indahnya Keberagaman Di Negeri Ku” to Increase Student Interest to Pancasila and Civic Education Subject - Rizki Nurhabibi (Randwick International of Education and Linguistics Science Journal, 2023)
This research aims to produce a Civics e-module with material on The Beauty of Diversity in My Country which can make it easier for fourth grade students to study at SD Negeri 100600 Sipogas. This research is a type of R&D research by adopting and modifying the development steps from Borg and Gall. The research instruments used were interview guidelines, questionnaires, observations and tests. The subjects in this research involved 3 lecturers as expert validators, 24 students as test subjects and a test of interest in learning. Research data analysis uses quantitative and qualitative data. The results of Pancasila and Civic Education e-module assessment The Beauty of Diversity in My Country from material experts got an average score of 4.17 with good criteria, language experts got a score of 93.75% with very decent criteria, design experts got an average score of 3.95 with good criteria, trial The initial field test got a percentage of 88.89% with the appropriate criteria, the field trial got a percentage of 97.23% with the appropriate criteria, the field test got a percentage of 95.58% with the appropriate criteria, and the pretest learning interest test got a mean score of 40.20. while the posttest interest in learning showed an average score of 74.79, so that students' interest in learning experienced an increase in the average score of 34.59. Overall, the results of the development of Pancasila and Civic Education e-module are said to be suitable as a learning medium. Apart from that, there is an increase in interest in learning after students use Pancasila and Civic Education e-module, showing that indicators of success of Pancasila and Civic Education e-module can make it easier for students to learn compared to just using teacher explanations and textbooks.